Avtonomno gibanje slepega v prostoru - iluzija ali realnost? - Amon, Sandra (Šport (Ljubljana), 2014)
The article presents a possibility of autonomous spatial movement of a blind person by using an innovative interface. For a better understanding there are several terms presented: orientation, mobility, muscle stimulation, cognition, emotional states, sensory system and concentration. The aim of this study was to determine what are the possibilities of autonomous movement of a blind person in a surrounding environment by using an innovative interface, hence more positive emotional status and social integration. With the descriptive exploratory case study multiple tests were performed - namely on a blind and a seeing person. In the case study measurements of mood states with the Brunel Mood Scale (BRUMS) were made. The test person in the case study is a 38 - year old blind man and in control case study the test person is a 30 - year old seeing man both with an active life style. The tests were consisted of ten succesive commands by using an innovative wearable interface for navigation. The results of this case study show that the navigation interface offers more possibilities for navigating blind people, presents an additional accessory for orientation in space and has a positive impact on emotional states.
Keywords: autonomous human movement; avtonomno gibanje; blindness; cognition; kognicija; mobility; mobilnost; orientacija; orientation; slepota; sport; šport